Pengaruh Keunggulan Atribut Produk Menu Masakan Terhadap Loyalitas Pelanggan Dengan Kepuasan Konsumen Sebagai Variabel Moderating - Koerniawan Hidajat; Royyani Hasanah (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2019)
Customer loyalty is an important role in increasing sales during a pandemic, and subsequently loyal customers will continue to believe in other products made by manufacturers, and will forever be loyal to producers or companies. the achievement of customer loyalty, namely the product attributes of the cuisine menu and customer satisfaction. This study aims to examine the effect of the superiority of the menu product attributes on customer loyalty which is moderated by consumer satisfaction. The population in this study were all employees of Kobexindo Tower, Artha Graha, and Diamond Fair. The data collection method in this study was a purposive sampling test which was adjusted to the Structural Equation Model (SEM) method, resulting in a total sample of 116 respondents. The data analysis method in this study is the outer model and inner model analysis method through an analytical tool in the form of Smart PLS version 3.0. The results showed that the product attributes of the menu have a positive and significant effect on customer loyalty, consumer satisfaction has a positive and significant effect on customer loyalty, and consumer satisfaction has the ability or magnitude to moderate the relationship between product attributes and customer loyalty.Keywords: Product Attributes of Cuisine Menu, Customer Loyalty, and Consumer Satisfaction